Financial and tax policy in the economic development of Kazakhstan - Аймурзина, Б.; Асилова A. (Journal of Economic Research & Business Administration, 2017)
The article analyzes the state and changes in GDP for the period 2006-2015, including the production of goods and services in recent years. Attention is paid to the dynamics of the tenge exchange rate for the US dollar between 2011 -2015. Specifies that in the present conditions the trend of development and deepening of integration processes in the world economy dictate the need for harmonization of financial and payment instruments and taxation, that requires a review of the existing financial system management. In this context, the main priority objectives of the fiscal and tax policy should be further growth in GDP with the obligatory direction to increase the production of products with high added value. Also, great attention should be paid to the further stabilization of the financial sector in Kazakhstan. It is necessary to pay attention to the socially necessary level of tax revenue in the revenue part of the state budget while maintaining the necessary level of economic potential of the business entities. There is a need to develop a system of management of non-tax revenues, based on the analysis of non-tax component of budget trends and management indicators non-tax revenues, enhance the efficiency of tax audits.